Statistical optimization of lipid production by the diatom Gyrosigma sp. grown in industrial wastewater - Natanamurugaraj, Govindan; Gaanty Pragas, Maniam; M. M., Yusoff; Mohd Hasbi, Ab. Rahim; Chatsungnoen, Tawan; Rameshprabu, Ramaraj; Chisti, Yusuf (Springer Netherlands, 2019)
The marine diatom Gyrosigma sp. was cultured in a medium comprised of inorganic nutrients dissolved in palm oil mill effluent (POME) wastewater. The production of lipids in the biomass was optimized using a statistical design of experiments in combination with the response surface method. The experimental factors were incident light level and initial concentrations of nitrate, phosphate, and silicate in the medium in batch culture. At 25 ± 2 °C, the maximum lipid content in the biomass harvested at the end of a 12-day batch culture was 70.7 ± 6.0% by dry weight for the following values of the experimental factors: an incident light level of 131 μmol photons m−2 s−1, a nitrate concentration of 1.8 mg L−1 (29.0 μM), a phosphate concentration of 6.8 mg L−1 (71.6 μM), and a silicate concentration of 10.1 mg L−1 (132.7 μM). Under the optimized conditions, the maximum dry mass concentration of the diatom was 560 mg L−1 on day 8 of a batch culture, declining to ~409 mg L−1 on day 12. For the 12-day batch operation, the final average productivities of the biomass and the lipids were 34.1 ± 5.5 mg L−1 day−1 and 24.1 ± 0.2 mg L−1 day−1, respectively. The fatty acids in the algal lipids were found to be as follows (%, w/w of total lipids): palmitic acid (48.6%), eicosapentaenoic acid (10.6%), myristic acid (8.1%), stearic acid (8.0%), linoleic acid (7.5%), oleic acid (6.4%), and linolenic acid (5.8%). The response surface model predicted the lipid content in the biomass with a high degree of confidence.